Apakah Gosip Bisa Menjadi Kontrol Sosial? - Meinarno, Eko A; Bagaskara, Sunu; Rosalina, Mely Putri Kurniati (Jurnal Psikologi: PITUTUR, 2011)
This study set out in the social life of the people  of  Indonesia.  This  issue  is  all  about gossip as social control. If all this gossip to talk bad about as far as is known, then the Foster (2004) explains that one function of gossip is to influence people. One form that seems extreme is social control. The existence of social control are expected to achieve harmony in social life.In  the  current  study  focused  on adolescents.  In  the  adolescent  phase  of  this development has wider social life and diverse. Patterns of friendship that extends also part of one´s  youth.  Another  important  point  is  very sensitive to adolescents evaluative information against him. Thus gossip as a tool for social control could be the entrance to evaluate the adolescents in their everyday lives. R e s e a r c h e r s   t a k e   a   s a m p l e   o f  approximately  250  adolescents  randomly sampling  with  this  type  of  random  sampling. The proportion of men and women equally, the median age was 18.58 years (SD = 1.79). In this study  used  self-report  measure  of  modality. Subtest function measurement using gossip as a tool to influence others from scale measuring GFQ (questionnaire Gossip Foster), composed by Eric foster (2004). As a result, 55.2 per cent of  participants  of  the  important  functions  of gossip influence others. However, if both sexes were  compared  results  were  not  found substantial  differences  (though  the  average higher for women). Using these results can be expected that most gossip, but does not control or at least influence other people. It could, the supervisory  functions  should  be  something concrete, not just talk about word of mouth.